Dexmedetomidine Does Not Affect Evoked Potentials During Spine Surgery. Issue 2 (April 2016) - Rozet, Irene; Metzner, Julia; Brown, Marcia; Treggiari, Miriam M.; Slimp, Jefferson C.; Kinney, Greg; Sharma, Deepak; Lee, Lorri A.; Vavilala, Monica S.
Abstract : Surv Anesthesiol 2016;60(2):89–90 Most common anesthetics, which usually function via γ-aminobutyric acid (GABA) mechanisms, suppress evoked potentials (EPs) during surgery. However, monitoring of multimodal EPs, including somatosensory EPs (SSEPs), motor EPs (MEPs), and visual EPs (VEPs), has been shown to improve neurologic outcome after spine surgery.